2023
DOI: 10.3390/su15064989
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Cascade Reservoirs on Streamflow, Drought, and Flood in the Jinsha River Basin

Abstract: The Jinsha River Basin (JRB) is the largest hydropower base in China, serving as the main source of the Western Route of China’s South-to-North Water Diversion Project. Under the influence of the reservoirs operation and climate change, the general hydrological regime in the JRB has been altered. Although the change process can be determined through a runoff time-series analysis and hydrological simulation, the individual impacts of the reservoirs have not been quantified. This study aimed to clarify the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…However, in the presence of large-scale regulating reservoirs upstream, their operation mitigates the increase in extreme runoff values caused by climate change, showcasing the peak-shaving effect of water engineering on river runoff [44]; therefore, no clear directional change in maximum runoff values is observed. Furthermore, attribution analysis of mean runoff changes (Table 8) indicates that large reservoirs have a storage effect on river runoff, reducing the long-term average runoff in the basin to some extent [45,46]. On the other hand, climate change has a positive impact on runoff, and its influence far exceeds that of reservoirs [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of large-scale regulating reservoirs upstream, their operation mitigates the increase in extreme runoff values caused by climate change, showcasing the peak-shaving effect of water engineering on river runoff [44]; therefore, no clear directional change in maximum runoff values is observed. Furthermore, attribution analysis of mean runoff changes (Table 8) indicates that large reservoirs have a storage effect on river runoff, reducing the long-term average runoff in the basin to some extent [45,46]. On the other hand, climate change has a positive impact on runoff, and its influence far exceeds that of reservoirs [47].…”
Section: Discussionmentioning
confidence: 99%
“…To enhance drought prevention and drought management in the basin, it is particularly vital to investigate the hydrological evolution of drought in the JRB. For example, Zhang et al [21] extensively examined how the Jinsha River Reservoir influences runoff, flooding, and drought patterns. By combining long short-term memory (LSTM) modeling with flood-drought assessment techniques, their study revealed important findings.…”
Section: Introductionmentioning
confidence: 99%